DK science : the definitive visual guide - Hart-Davis, Adam. (New York : New York : DK, 2011)
"This remarkable reference book tells the story of scientific progress from the invention of the wheel to 21st century climate solutions. It captures every key moment of discovery, and shows how the concepts, the inventions, and the individuals behind them have changed our world. By using amazing illustrations and accessible text, Science explains even the most complex topics more clearly than ever before"--P. [4] of cover.
The dawn of science : prehistory to 1500 -- Renaissance & Enlightenment : 1500-1700 -- The Industrial Revolution : 1700-1890 -- The Atomic Age : 1890-1970 -- The Information Age : 1970 onward.
Includes index.
Keywords: Science -- Encyclopedias